2010
DOI: 10.1073/pnas.0905901107
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular dynamics of T cell immunological synapses and kinapses in lymph nodes

Abstract: In vitro studies have revealed that T cell activation occurs during the formation of either dynamic or stable interactions with antigenpresenting cells (APC), and the respective cell junctions have been referred to as immunological kinapses and synapses. However, the relevance and molecular dynamics of kinapses and synapses remain to be established in vivo. Using two-photon imaging, we tracked the distribution of LAT-EGFP molecules during antigen recognition by activated CD4 + T cells in lymph nodes. At steady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 54 publications
3
76
0
Order By: Relevance
“…This hypothesis is supported by the finding that recently activated T cells forming kinapses in vivo engage their TCR efficiently but fail to accumulate the signaling molecule LAT at the IS and emit only short calcium spikes. 29 Since an initial wave of [Ca 2+ ]i is required for the stop signal 30 and since the [Ca 2+ ]i signaling pattern regulates the shape and stability of T cells contacting APC, 31 it may be argued that a primary defect in calcium mobilization is responsible for the phenotype of WAS T cells. However, ]i strongly indicates that the abnormal calcium mobilization pattern is a consequence rather than a cause of the disorganized WAS T-cell IS.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the finding that recently activated T cells forming kinapses in vivo engage their TCR efficiently but fail to accumulate the signaling molecule LAT at the IS and emit only short calcium spikes. 29 Since an initial wave of [Ca 2+ ]i is required for the stop signal 30 and since the [Ca 2+ ]i signaling pattern regulates the shape and stability of T cells contacting APC, 31 it may be argued that a primary defect in calcium mobilization is responsible for the phenotype of WAS T cells. However, ]i strongly indicates that the abnormal calcium mobilization pattern is a consequence rather than a cause of the disorganized WAS T-cell IS.…”
Section: Discussionmentioning
confidence: 99%
“…GFP + OT-I CD8 + T cells were preactivated in vitro for 72 h using anti-CD3/CD28 beads (Dynal) in the presence of 25 U/mL recombinant IL-2 (Roche) and allowed to migrate in 6-μm-wide microchannels coated with pMHC (11). In some experiments, T cells were retrovirally transduced to express GFP-centrin or LAT-GFP (26,27) and stained with 1 μg/mL Hoechst 33342 (Life Technologies). In brief, OT-I T cells were activated for 2 d with anti-CD3/CD28 beads (Dynal) in the presence of 25 U/mL recombinant IL-2 (Roche) and spin-transduced at day 2 and day 3 after activation as previously described (27).…”
Section: Methodsmentioning
confidence: 99%
“…In some experiments, T cells were retrovirally transduced to express GFP-centrin or LAT-GFP (26,27) and stained with 1 μg/mL Hoechst 33342 (Life Technologies). In brief, OT-I T cells were activated for 2 d with anti-CD3/CD28 beads (Dynal) in the presence of 25 U/mL recombinant IL-2 (Roche) and spin-transduced at day 2 and day 3 after activation as previously described (27). When indicated, EGTA (2.5 mM; Sigma), CK666 (25 μM; Tocris), or PP2 (20 μM; Calbiochem) was added to the culture medium during the migration assay.…”
Section: Methodsmentioning
confidence: 99%
“…The only dynamic molecular imaging in the LN to date has shown that LAT (linker of activated T cells) localizes to the contact interface during stable interactions of activated T cells with antigen-bearing B cells but not during motile interactions of activated T cells with DCs (Azar et al, 2010). Static imaging of CD43-GFP fusion proteins also demonstrated T cell-DC interactions that exclude CD43 from the contact interface (Stoll et al, 2002), which is consistent with this molecule's position in synapses formed in vitro.…”
Section: Expression and Functionality Of The Ot-i-gfp Tcrmentioning
confidence: 99%